Le cluster de Rio Verde ou l’interaction de l’agrobusiness et du développement territorial au Brésil - Thierry Bonaudo; René Poccard-Chapuis; Cassia Coutinho; Jean-François Tourrand; Laura Duarte (Confins)
The globalization of the economy boots a strong development of an agribusiness model based on the integration of intensive and specialized farming systems in agribusiness companies driving input supply, technique and economic aspects through global trade channels. This model draws new patterns of local development where farmers and local people interact with global players. The county of Rio Verde (Goías State, Brazil) is a good example of this model, with the gradual development of an agribusiness cluster based on corn and soybean then an intensive poultry production coordinated by Brasil Foods. In the 2000s, the strong development of sugar cane production interacts with this dynamics driven by Brasil Foods questioning directly the model of local development. The authors analyze this local and regional development through the building the agribusiness cluster. The building of the Rio Verde cluster based on global players has a substantial improvement in the main indicators of socio-economic development. However, the externalities are high environmental pressure and governance mechanisms dominated by large private firms and funded in large part by the government.